2019
DOI: 10.1101/816405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Growth under high light and elevated temperature affects metabolic responses and accumulation of health-promoting metabolites in kale varieties

Abstract: 19Plants are highly sensitive to changes in the light environment and respond to alternating light 20 conditions by coordinated adjustments in foliar gene expression and metabolism. Here we 21 assessed how long-term growth under high irradiance and elevated temperature, a scenario 22 increasingly associated with the climate change, affects foliar chemical composition of 23 Brassicaceous plants. Transcript profiling of Arabidopsis suggested up-regulation of 24 phenylpropanoid metabolism and down-regulation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…In kale plants, the accumulation of glucosinolates, total phenolics, and flavonoids has is stimulated by exposure to radiation. Alegra et al [135] reported a significant increase in aliphatic glucosinolates in Half Tall and Black Magic kale radiated after two days of germination with high light (800 µmol photons/m 2 s). Black Magic showed an increase in glucoraphanin (150%, 100 nmol/g FW), glucoerucin (350%, 1.8 nmol/g FW), and total aliphatic glucosinolates (175%, 110 nmol/g FW) by high light treatment, while Half Tall displayed the same response to treatment in glucoberverin (2%, 6 nmol/g FW), glucoraphanin (400%, 20 nmol/g FW), glucoerucin (100%, 0.5 nmol/g FW), and total aliphatic glucosinolates (66%, 100 nmol/g FW).…”
Section: Radiation As An Abiotic Stressormentioning
confidence: 99%
“…In kale plants, the accumulation of glucosinolates, total phenolics, and flavonoids has is stimulated by exposure to radiation. Alegra et al [135] reported a significant increase in aliphatic glucosinolates in Half Tall and Black Magic kale radiated after two days of germination with high light (800 µmol photons/m 2 s). Black Magic showed an increase in glucoraphanin (150%, 100 nmol/g FW), glucoerucin (350%, 1.8 nmol/g FW), and total aliphatic glucosinolates (175%, 110 nmol/g FW) by high light treatment, while Half Tall displayed the same response to treatment in glucoberverin (2%, 6 nmol/g FW), glucoraphanin (400%, 20 nmol/g FW), glucoerucin (100%, 0.5 nmol/g FW), and total aliphatic glucosinolates (66%, 100 nmol/g FW).…”
Section: Radiation As An Abiotic Stressormentioning
confidence: 99%
“…The deposition of glucosinolates in growing plants and their distribution to plant organs are significantly affected by environmental factors [ 26 ], with temperature being one of the key factors. Several studies have been conducted to determine the process and effects of temperature on seed germination, physical development, flower formation, and yield [ 27 , 28 , 29 , 30 ]. However, physiological processes and their integration are sped up under higher temperatures with both positive and negative effects.…”
Section: Introductionmentioning
confidence: 99%